THEORETICAL AND PRACTICAL INTEGRATION OF THE USE OF GAMES IN VOCABULARY TEACHING - Dilnoza Mamanova Abdurashid qizi; Nigina Amirova O‘ktam qizi; Farida Abdumannonova Komiljon qizi (TADQIQOTLAR, 2025)
Annotation: This article thoroughly analyzes the theoretical and practical foundations of using game technologies in the vocabulary teaching process. Game methods are highlighted in connection with the psychology of language learning, cognitive processes, motivation, memorization mechanisms, and their role in the development of communicative competence. During the study, the effectiveness of vocabulary acquisition through games, the advantages of digital platforms, role- playing games, problem-situational games, strategic games, and language games added to the lesson process are demonstrated with practical examples. The article analyzes, based on statistical data, the influence of game methods on the quality of education, students’ active participation, the level of assimilation, motivation indicators, and changes in the teacher’s pedagogical skills. The conclusion contains proposals for future research.